STRATEGIC MECHANISMS THAT WILL FACILITATE MYPE EXPORTS TO THE COUNTRIES OF FREE TRADE AGREEMENTS-NAFTA FOR THE COUNTRY'S DEVELOPMENT - Flores Konja, Adrian Alejandro (2010)
The article presents the main conclusions and recommendations of the research the same subject and title, and was selected by the Research of our House of Studies; in addition, we present the research objectives, methodology and the different situations that arose during the investigation. The research used primary sources, collected through surveys administered with the help of a group of students of the Faculty to the guilds of MYPES, and secondary sources too. The limitation was the impossibility practical of reach even if indirectly to the informal MSEs, obtaining direct information of the SMEs only formal, more modern and organized. As a result of this investigation, it knows that the neitre the MYPES have not used the drawback, other mechanisms promoters of exports, as an incentive to internationalize, because the vast majority MYPES not been formalized. Secondary immediate causes, is that managers of MYPES are unaware of the benefits of the drawback of insufficient dissemination, which lack trained personnel for implementation of the drawback, and also lack of adequate cost structure to follow this and other schemes of export promotions .The incentives concluded on the necessity that the state should support MYPES through building infrastructure that reduces the existing cost overruns and severe measures lowering the cost of money, along an industrial plan, to propose a true national competitiveness.